Respuesta :
[tex] \dfrac{1}{2}x- 4 - (\dfrac{5}{6} x - 4 )[/tex]
[tex] = \dfrac{1}{2}x- 4 - \dfrac{5}{6} x + 4 [/tex]
[tex] = \dfrac{1}{2}x - \dfrac{5}{6} x [/tex]
[tex] = \dfrac{3}{6}x - \dfrac{5}{6} x [/tex]
[tex] = -\dfrac{2}{6}x [/tex]
[tex] = -\dfrac{1}{3}x [/tex]
------------------------------------------------------
Answer : - 1/3 x
------------------------------------------------------
To check:
[tex] \dfrac{5}{6}x - 4 + (- \dfrac{1}{3}x ) = \dfrac{5}{6}x- \dfrac{1}{3}x-4= \dfrac{5}{6}x- \dfrac{2}{6}x-4 = \dfrac{3}{6}x-4 = \dfrac{1}{2}x-4 [/tex]
[tex] = \dfrac{1}{2}x- 4 - \dfrac{5}{6} x + 4 [/tex]
[tex] = \dfrac{1}{2}x - \dfrac{5}{6} x [/tex]
[tex] = \dfrac{3}{6}x - \dfrac{5}{6} x [/tex]
[tex] = -\dfrac{2}{6}x [/tex]
[tex] = -\dfrac{1}{3}x [/tex]
------------------------------------------------------
Answer : - 1/3 x
------------------------------------------------------
To check:
[tex] \dfrac{5}{6}x - 4 + (- \dfrac{1}{3}x ) = \dfrac{5}{6}x- \dfrac{1}{3}x-4= \dfrac{5}{6}x- \dfrac{2}{6}x-4 = \dfrac{3}{6}x-4 = \dfrac{1}{2}x-4 [/tex]